ANALISIS PERBANDINGAN LOYALITAS KONSUMEN BLACKBERRY SEBELUM DAN SESUDAH ADANYA BBM FOR ANDROID, DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Gabor Nemeth; Eka Fitriyani (Universitas Mercu Buana, 2015)
This research aims to analyze the comparison of consumer loyalty before and after the emergence of BBM For Android and the factors that influence it.This research is a comparative study. The analysis tool in research methods used are test instruments, different test and factor analysis test. Research results with different test T-Paired shows that the value of T count (5.571) > T table (0.676) and the Sig. (0,000) <a (0.05) which means that there is a difference of consumer loyalty before and after the emergence of BBM For Android, which is where the differences it shows a decrease of loyalty with an average decrease of 4,243. And analysis of test factors using the KMO Bartlett's test said that factors used tested the feasibility with the value 0,875, and the most dominant factor in influencing consumer loyalty is the satisfaction felt by consumers and Brand Image. Suggestions for further research, should expand the factors research and improved research in order to obtain more accurate results. Keywords : Consumer Loyalty, Factors of Consumer Loyalty